Use of the Animal 4D Application to Improve English Vocabulary for Elementary School Children - Rahmawati, Lailia (Scientechno: Journal of Science and Technology, 2024)
Utilization of the animal 4D application as an approach to increasing English vocabulary for elementary school children. However, problems also often arise, namely that a teacher's efforts to collaborate with students are very minimal, and managing responsibilities is difficult to implement because students have different points of view regarding the use of the Animal 4D application. Then there are other problems that also have an impact on students' academic knowledge, so that students' thinking becomes complicated to understand. Apart from that, raising student enthusiasm requires a supportive environment, but high academic demands are a challenge for students to face new concepts. This research aims to examine the influence of using the Animal 4D application to improve the English vocabulary of elementary school children. Apart from that, researchers also admit that in the educational environment, especially elementary schools, it is very necessary to apply English vocabulary which becomes a reference for these schools to increase the use of the animal 4D application. This research method uses a quantitative method, namely this method is an indication for respondents that this research is in the form of numbers. This was obtained through observations in the classroom and outside the classroom to find out how collaboration and cooperation between teachers and students went well during learning based on the Animal 4D application. Next, the researchers conducted interviews with teachers and students regarding the use of the animal 4D application to improve elementary school children's English vocabulary, as well as collecting quantitative data by distributing online-based questionnaires in the form of Google forms. The results of this research explain that the use of the animal 4D application has an impact on the motivation of elementary school students. When students are able to collaborate with other students, these students are able to develop innovative thinking skills and foster a sense of caring for each other. The conclusion of this research shows that a combination of good collaboration in learning based on the use of the Animal 4D application has great potential to increase students' creativity in mastering English vocabulary.